EFFECT OF PERSUASIVE ABILITY, TECHNICAL ABILITY AND WORK ETHICS OF FIELD EXTENSION STAFF (PPL) ON SATISFACTION OF BROILER CHICKEN BREEDERS AT PT. SIERAD PRODUCE - Evita Vibriana (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
In the global economic era requires business breakthrough efforts to proactively consolidate themselves in order to strengthen competitive advantage, which no longer relies on comparative advantage in the field of raw materials, but also competitive advantages that can be achieved if business people have organizational competence, which means that the businessman can improve his performance. One way to improve performance is through improving human resources. One of the business businesses of PT. Sierad Produce, Tbk is a partnership farming system, where the cutting edge of this business is the Field Extension Officer (PPL), this field employee whose duties and responsibilities are to provide technical direction in the field to the company's breeders about how to run broiler chicken management in accordance with the standards applied by the company to produce good and correct chicken performance. So that the staff of the field extension staff are satisfied with business partners.